Mayo clinic on osteoporosis : [keeping bones healthy and strong and reducing the risk of fracture] - Hodgson, Stephen (Stephen F.) (Mayo Clinic ; Distributed to the Book trade by Kensington Pub., 2003)
A compendium of information on osteoporosis includes symptoms, risks, prevention, and treatment, and a comprehensive guide combines current medical research with a simple diet and exercise program that promotes bone health.